The Efficiency of Zakat Collection and Distribution in Indonesia - Azzahrah Izzatul Muslimah; Nashr Akbar (JESI (Jurnal Ekonomi Syariah Indonesia), 2021)
This study aims to compare the level of efficiency of zakat collection and distribution by Zakat Institution in Indonesia. It is hoped that this research can find out what factors affect inefficiencies in the process of collecting and distributing zakat by National Zakat Institution. This study is quantitative research using Data Envelopment Analysis (DEA) with output orientation. Financial statements of 8 zakat institutions during 2012-2018 were analyzed. In zakat collection the input variables are administrative and general expenses, amil fee, number of branches, and socialization cost while the output variable is zakat collected. In terms of zakat distribution process, the input variables are administrative and general expenses, amil fee and zakat collected against the output variable, zakat distributed.  This study found that zakat collection has a higher efficiency score (72.32%) compared with zakat distribution (61.45%). Using potential improvement analysis, zakat institutions are adovacated to do more in zakat collection while handling inefficient socialization cost. In the same time, they should distribute more zakat funds while optimizing their staff/amil in zakat distribution.